Temporal issues in person–organization fit, person–job fit and turnover: The role of leader–member exchange. (December 2016) - Boon, Corine; Biron, Michal
Person–environment fit has been found to have significant implications for employee attitudes and behaviors. Most research to date has approached person–environment fit as a static phenomenon, and without examining how different types of person–environment fit may affect each other. In particular, little is known about the conditions under which fit with one aspect of the environment influences another aspect, as well as subsequent behavior. To address this gap we examine the role of leader–member exchange in the relationship between two types of person–environment fit over time: person–organization and person–job fit, and subsequent turnover. Using data from two waves (T1 and T2, respectively) and turnover data collected two years later (T3) from a sample of 160 employees working in an elderly care organization in the Netherlands, we find that person–organization fit at T1 is positively associated with person–job fit at T2, but only for employees in high-quality leader–member exchange relationships. Higher needs–supplies fit at T2 is associated with lower turnover at T3. In contrast, among employees in high-quality leader–member exchange relationships, the demands–abilities dimension of person–job fit at T2 is associated with higher turnover at T3.